Contribution of direct-drinking water to calcium and magnesium and the influence on the height in school-age children - Gu, Hongru; Gong, Yijing; Li, Zhao; Zhang, Yanqiu; Wu, Jin; Wang, Yi; Ni, Min; Zhang, Jun; Jiang, Hai (Frontiers in Nutrition, 2024)
Objective: To estimate the contribution of direct-drinking water provided in school to dietary intake (DI) and recommended nutrient intake (RNI) of calcium and magnesium, and to explore its influence on the height in school-age children.Tap water and direct-drinking water samples were collected from schools in Taicang City to test the contents of calcium and magnesium, and compared by one-way ANOVA and post-hoc test.Contribution rates of direct-drinking water to DI and RNI were calculated by using the contents of calcium and magnesium and data from the Nutrition and Health Status Survey 2021. A retrospective cohort was conducted among 4850 first-grade children consuming direct drinking water in Taicang City from 24 primary schools in 2019. Group 1 (1,070 boys and 946 girls) consumed UF-process water with normal calcium and magnesium contents and Group 2 (1,548 boys and 1,286 girls) consumed NF/RO-process water with very low calcium and magnesium contents. During 2019-2023, the height and height growth were analyzed with the Student's t-test.The highest calcium content was examined in tap water samples, followed by directdrinking water samples supplied through a UF, NF and RO system (F=1,227.725, P<0.001). The highest magnesium content was examined in water supplied through a UF system, followed by that through a tap, NF and RO system (F=146.504, P<0.001). Calcium and magnesium contents in directdrinking water supplied through a UF system changed little compared with those in tap water, which were significantly reduced in direct-drinking water supplied through a NF and RO system. The contribution rates of direct-drinking water to DI of calcium and magnesium were 8.95% and 2.78%, respectively, and those to RNI of calcium and magnesium were 2.63% and 1.96%, respectively. There were no significant differences in the height and height growth of first-grade children drinking water supplied through the UF system versus NF/RO system (P>0.05).Direct-drinking water processed through a NF or RO system should be cautiously adopted in primary and secondary schools. A UF system is preferred in schools where no health concerns are associated with water quality.